Assessment of rhizome yield of local Indonesian turmeric (Curcuma longa L.) during two growing seasons - REVIANA AULIA; HARIS MAULANA; YOSHUA LIBERTY FILIO; NURUL AMELIA SHAFIRA; PUTRI ARDHYA ANINDITA; TARKUS SUGANDA; VERGEL CONCIBIDO; AGUNG KARUNIAWAN (Society for Indonesian Biodiversity, 2022)
Abstract. Aulia R, Maulana H, Filio YL, Shafira NA, Anindita PA, Suganda T, Concibido V, Karuniawan A. 2022. Assessment of rhizome yield of local Indonesian turmeric (Curcuma longa L.) during two growing seasons. Biodiversitas 23: 2534-2543. In Indonesia, rhizome yield evaluation across diverse growing seasons is very useful for selecting turmeric genotypes that have the potential to be developed into commercial varieties. Evaluation using multiple measurements has high accuracy. This study aimed to select turmeric genotypes based on differences in agro-morphological traits, identify genotypes by season interactions (GEIs), and select stable and high-yielding turmeric during two seasons. The study was conducted for two growing seasons (Planting Season 1 in January - October 2019 and Planting Season 2 in January - October 2020) using an augmented design. Cluster analysis based on agro-morphological traits was used to select turmeric genotypes based on their proximity. A combined analysis of variance (ANOVA) was used to estimate the effect of GEIs on rhizome yield and yield attributes. Rhizome yield evaluation was analyzed using parametric and nonparametric measurements. The results showed that twenty-five turmeric genotypes were selected based on agro-morphological differences. GEIs caused the variation of rhizome yield with a contribution of 34.88%, and yield attributes of 7.04% for weight per plant (WPP), 10.97% for rhizome width (RW), 11.95% for Petiole length (PL), 47.25% for lamina length (LL), and 25.44% for lamina width (LW). The results of parametric and nonparametric measurements selected six genotypes of turmeric into ideal groups, namely G4 (CL-12), G6 (CL-20), G9 (CL-30), G12 (CL-37), G22 (CL-82), and G26 (Cek 1). They can be developed as superior local commodities and used as breeding materials for turmeric plants in the future.